Development of Intermediate Temperature (550 - 650oC) Metal Supported Solid Oxide Fuel Cells (SOFCs) Using Plasma Processes. (2nd June 2015) - Rupa, Pantula K. P.; Goli, V. R.; Balasubramanian, Krishnamurty; Tomov, R I; Kumar, R Vasant; Glowacki, B A; Krishnan, Venkatesan Venkata
Abstract : An entire cycle for fabricating a metal supported cell is developed, using porous SS430L as anode substrate, NiO-GDC as the anode, GDC as electrolyte and LSCF as cathode, as follows - - Tape Casting of porous SS430L substrate layers, followed by vacuum sintering (1100 C)- Brush painting of anode (NiO + GDC) layers, followed by a high heat flux treatment to induce rapid sintering - Plasma Spray (powder) deposition of GDC electrolyte layer leading to sintering- Ink-Jet printing of GDC colloidal suspension to give better finish to the 'rough' electrolyte surface, followed by high heat flux treatment- Brush painting of cathode (LSCF) layers on the electrolyte surface followed by high heat flux treatment The cells are characterized for their microstructure and have shown highly dense electrolytes, and fine microstructures for anodes and cathodes. Process refinements are underway (with electrochemical characterization) to enhance cell performance and stack assembly.